Patterns of Rainfall Insurance Participation in Rural India - Giné, Xavier (World Bank, 2012)
Take-up of an innovative rainfall insurance policy offered to smallholder farmers in rural India decreases with basis risk between insurance payouts and income fluctuations, increases with household wealth, and decreases with binding credit constraints. These results are consistent with the predictions of a simple neoclassical model with borrowing constraints. Other patterns are less consistent with the benchmark model. For example, participation in village networks and measures of familiarity with the insurance vendor are strongly correlated with insurance take-up decisions, and risk-averse households are less, not more, likely to purchase insurance. These results may reflect household uncertainty about the product, given their limited experience with it.